Pengaruh Pemberian Pakan Alami Daphnia sp. yang diperkaya dengan Tepung Spirulina Terhadap Kelangsungan Hidup dan Pertumbuhan Benih Ikan Cupang (Betta sp.) - Maulana, Teuku Alrian; Komariyah, Siti; Febri, Suri Purnama; Harahap, Antoni (Fakultas Pertanian Universitas Samudra, 2024)
The aim of this research is to analyze the influence of Daphnia sp. enriched with Spirulina flour on the survival and growth of Betta fish seeds (Betta sp.) and determine the best dosage of Daphnia sp. that is enriched with Spirulina flour on the survival and growth of Betta fish seeds (Betta sp.). The method used in this research is an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications for each treatment, namely, P1 Daphnia sp. enriched with spirulina flour 1 g/L, P2 Daphnia sp. enriched with spirulina flour 2 g/L, P3 Daphnia sp. enriched with spirulina flour 3 g/L, and P4 Daphnia sp. enriched with spirulina flour 4 g/L. Daphnia sp. enriched with Spirulina at different doses in Betta fish seeds (Betta sp.) had a significant effect (P<0.05) on survival and growth performance. The greater the dose of Spirulina flour enriched in Daphnia sp. the higher the survival and growth performance of Betta fish seeds (Betta sp.), and the best treatment is P4 with a dose of 4 g of Spirulina.